Optical Coherence Tomography With Gapped Spectrum - Nanshuo Wang; Xinyu Liu; Xiaojun Yu; Si Chen; Shi Chen; Linbo Liu (IEEE Photonics Journal, 2019)
The axial resolution of optical coherence tomography (OCT) is determined by the spectral shape and bandwidth of the detected light, which are limited by the gaps in the wavelength range of illumination, transmission, and detection. In this paper, we demonstrate that the axial resolution deteriorated by gaps in OCT spectra can be restored by adopting the gapped amplitude and phase estimation (GAPES) method. GAPES estimates the missing parts between separated spectral bands and obtains the axial profile of tissue with reduced sidelobe artifacts compared to the gapped spectra and significantly improved axial resolution over the individual bands. This technique may make it possible to combine spectrally separated sources and detectors to improve axial resolution in OCT images.